تطبيق الإدارة بالأهداف وعلاقتها بأداء العاملين بمنظمات الأعمال الليبية (دراسة ميدانية على شركتي الخليج العربي لتسويق النفط والنهر لتصنيع الأنابيب) - عبدالله الخفيفي, مبروكة; يوسف المنصوري, فاطمة (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى معرفة علاقة تطبيق الإدارة بالأهداف على أداء العاملين بمنظمات الأعمال الليبية، وقد تكون مجتمع الدراسة من منظمات الأعمال الليبية والتي مقارها بمدينة بنغازي وقد تم تطبيق الدراسة على شركتي الخليج العربي والنهر لتصنيع الأنابيب، اختيرت منه عينة عشوائية طبقية قوامها (43) مديراً ورئيس قسم. وقد توصلت الدراسة إلى أن مستوى الإدارة بالأهداف بأبعادها الثلاثة كانت منخفضة المستوى، وكذلك مستوى أداء العاملين كان منخفض، كما أظهرت النتائج أن هناك علاقة موجبة لتطبيق الإدارة بالأهداف على أداء العاملين، كما توجد أيضاً علاقة ارتباطية بين أبعاد الإدارة بالأهداف وأداء العاملين في منظمات الأعمال الليبية. This study aims to know the relationship of the application of management with the objectives on the performance of workers in Libyan business organizations. The study population may be Libyan business organizations based in Benghazi. The study was applied to the Arabian Gulf and the river pipes manufacturing companies, from which a simple random sample of (43) administrators and head of department was selected. The study found that the level of management of the objectives in all three dimensions was low, as well as the level of performance of the staff was low level, the results showed that there is a positive relationship between the application of management and objectives on the performance of employees, and there is also a correlation between the dimensions of management with objectives and the performance of workers in Libyan business organizations
The Application of Management with the Objectives on the Performance of Workers in Libyan Business Organizations (Field Study on the Arabian Gulf and the River Pipes Manufacturing Companies)
مقال
Keywords: الإدارة بالأهداف، أداء العاملين، منظمات، شركة الخليج العربي، النهر لتصنيع الأنابيب.